2001
DOI: 10.1161/hh1901.098735
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18/Interleukin-18 Binding Protein Signaling Modulates Atherosclerotic Lesion Development and Stability

Abstract: Abstract-Interleukin (IL)-18 is the interferon-␥-inducing factor and has other proinflammatory properties. The precise role of IL-18 in immunoinflammatory diseases remains poorly understood. In this study, we show that in vivo electrotransfer of an expression-plasmid DNA encoding for murine IL-18 binding protein (BP) (the endogenous inhibitor of IL-18) prevents fatty streak development in the thoracic aorta of apoE knockout mice and slows progression of advanced atherosclerotic plaques in the aortic sinus. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
246
1
12

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 350 publications
(277 citation statements)
references
References 26 publications
18
246
1
12
Order By: Relevance
“…[37][38][39] Mallat et al had found that IL-18 binding protein can reduce atherosclerosis. [40] In our study, the plasma IL-18 level was reduced after six months of HDF, which may result in less IL-18 related atherosclerosis.…”
Section: Discussionsupporting
confidence: 51%
“…[37][38][39] Mallat et al had found that IL-18 binding protein can reduce atherosclerosis. [40] In our study, the plasma IL-18 level was reduced after six months of HDF, which may result in less IL-18 related atherosclerosis.…”
Section: Discussionsupporting
confidence: 51%
“…Serial sections of the aortic sinus were assayed for lipid deposition and collagen detection (with oil red O and sirius red, respectively; see Figure). 11 Immunohistochemistry was performed with the use of a rat anti-mouse macrophage antibody, clone MOMA-2 (Biosource International), a polyclonal goat anti-CD3⑀ antibody (Santa Cruz), a monoclonal anti-␣-smooth muscle actin, clone 1A4 (Sigma), or a goat polyclonal anti-CD31 antibody (Santa Cruz). Computerized quantifications were performed with the use of Histolab software.…”
Section: Quantitative Assessment Of Atherosclerotic Lesion Size and Cmentioning
confidence: 99%
“…The IL-18 receptor (IL-18R) complex consists of two receptor chains: a ligand-binding chain termed the IL-18R␣ chain and a coreceptor termed IL-18R␤ chain; both chains are required for signaling. Using specific neutralization of IL-18 activity, there is a role for IL-18 in rheumatoid arthritis (8,9), ischemic renal (10), and heart disease (11), as well as atherosclerosis (12).…”
mentioning
confidence: 99%